REAKSI PASAR TERHADAP PENGUMUMAN EMPLOYEE STOCK OWNERSHIP PROGRAM - Herdinata, Christian (UNIVERSITY OF MERDEKA MALANG, 2012)
In Indonesia, the increasing of Employee Stock Ownership Program (ESOP) was relative known new, so itneeded any evidence for the market reaction in Indonesia stock exchange. From the latest problem, the purposeof this research was to know how the market reaction for the announcement of ESOP in Indonesia StockExchange. Samples on this research were the companies which were listed in BEI that had announced ESOP forperiod January 1st, 2000 December 31st, 2010. Analysis technique on hypotesis test related with marketreaction for ESOP announcement was done by event study to calculate abnormal return. Research resultshowed that market tended to ignore ESOP announcement. And it meant that ESOP announcement was notconsidered as a signaling, which gave a good information for the investor in Indonesia to achieve profit.